Perceiving Destination Through Animated GIFs: A Mixed Method Design for Multifaceted Image Assessment. (January 2023) - Li, Huahua; Li, Mimi; Lin, Guyang; Qiu, Hanqin
The notion of multifaceted image, composed of cognitive, affective, and sensory dimensions, has attracted growing scholarly interest in recent years. However, general understanding of the roles of the senses (i.e., sight, hearing, taste, smell, and touch) in image processing remains scarce. Little attention has also been paid to the effects of visual stimuli related to design features on the construction of multifaceted image. This study investigated viewers' perceived multifaceted destination image upon exposure to different photo formats (i.e., animated vs. static). A mixed method approach was employed to collect data using a between-subjects experimental design. Findings revealed that moving visual presentation exert stronger impacts on three image dimensions in several aspects and associations were also observed between photo contents and sensory arousal. Results enrich the body of knowledge on destination image in terms of image structure and the features of visual stimuli. Practical implications are discussed as well.